(untitled) (Medico Legal Update, 2020)
This research discusses the implication of the local regulation revocation towards the economic and health condition in a number of regions in Indonesia. And also, some of the cases which resulted in the implication conditions. This article was the result of a doctrinal study with literature review study and secondary data. The result of the research shows that (i) there is a government’s authority in revoking Perdas; (ii) the revocation of the local regulations in certain regions exerts adverse effect on the economy and healthcare. This article suggests that there is a need for the development of Perda with high-quality substances so that it can cope with the implication of legal regulations.